Desain Terbaru Sistem Manajemen Pegawai Negeri Sipil Di Indonesia (Telaah Kritis: Paradigma Baru"The New Public Service") - M Nur Budiyanto (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2005)
This brief article represent the idea brainstorming and interesting offers on submiting various alternative about the new design of management system of civil servant that proposed by observer and bureaucrats but apparently it can not touch the problems that most basic, detailed and profound in characters. For the policy makers both at central or district, should "immediate" making review even if needed performed special research on correction and completion upon the existing weakness at the management system of civil servant in Indonesia such as those suggested in this article.